Pengaruh Perdagangan Global Terhadap Sektor Pertanian Lokal - Samosir, Maylan Andreas; Hernosa, Siswa Panjang (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2025)
This research aims to explore the impact of global trade on the local agricultural sector in Indonesia. In recent years, the agricultural sector has demonstrated remarkable resilience, even amidst global crises such as the COVID-19 pandemic, during which agricultural exports increased despite challenges from cheaper and higher-quality imported goods. The study also identifies challenges faced by local farmers, including price fluctuations and declining competitiveness due to trade liberalization and the establishment of the ASEAN Economic Community (AEC). By utilizing data from the Ministry of Agriculture and analyzing relevant literature, this research aims to provide deeper insights into both the positive and negative effects of international trade on the Indonesian agricultural sector, as well as recommendations for enhancing the competitiveness of local agricultural products in the global market.